NEW SPECIES OF AGRILUS FROM NICARAGUA AND COSTA RICA (COLEOPTERA, BUPRESTIDAE) - Gianfranco Curletti (Fragmenta entomologica, 2010)
Five new species of the genus Agrilus Curtis, 1825 from Costa Rica and Nicaragua are described: A. barriesi n. sp., A. maesi n. sp., A. ursus n. sp., A. tyrannus n. sp. and A. pumilio n. sp.